Engineering ‘extracellular matrix factories’ to study how the extracellular microenvironment regulates gene expression - Tomlin, Hannah (2021)
The extracellular matrix (ECM) is a specialised scaffold as well as a biochemical signalling platform for cells. The ECM plays a key role in gene regulation, with components such as tenascin-C (TN-C) being implicated in post-transcriptional regulation of inflammatory genes. However, the lack of physiologically relevant, healthy human ECM models has hindered the establishment of how specific ECM components regulate gene expression. Here, a human BJ skin fibroblast-derived ECM model was therefore developed combining cell-derived matrix (CDM) technologies with CRISPR/Cas9 genome editing. Assessment of fibroblast CDMs at the protein level by immunostaining and western blotting revealed the CDM contained collagen 1, collagen 3, fibronectin and glycosaminoglycans (GAGs). Microscopy techniques demonstrated a three-dimensional, 45 µm thick CDM. In addition, a protocol to effectively remove fibroblasts and DNA was optimised to obtain a non-immunogenic decellularised ECM substrate. FACs analysis confirmed the skin fibroblast CDM supported normal differentiation of primary human monocytes into macrophages and was a suitable culture substrate. Furthermore macrophage expression of LPS-induced miRNAs, including miR-155, was more stringently regulated when cultured on CDMs compared to plastic. Next, TNC KO fibroblasts were engineered via CRISPR/Cas9 gene editing to result in a fibroblast-derived ECM model that lacked TN-C. This was confirmed at the DNA, RNA and protein level. This allowed us to establish, for the first time in humans, that ECM-associated TN-C drives macrophage miR-155 expression in response to LPS. Furthermore, we identified that TNC¬ expression is linked to normal cell architecture, and that a lack of TNC leads to actin cytoskeleton dysregulation, premature cell aging, subsequent cell cycle arrest and senescence in fibroblasts, as confirmed by light microscopy, β-galactosidase staining, F-actin staining and RNA-Seq. Candidate molecules specifically responsible for this effect have been identified but require validation. This model highlights an ECM-dependent regulatory mechanism of inflammation and could highlight novel targets for the treatment of diseases resulting from ECM alteration. Furthermore, this ECM model could be utilised as a biological tool, fully customisable and amenable to genetic modifications of other ECM proteins to allow the elucidation of how ECM components regulate gene expression and cell behaviour in health and disease, whilst also replacing the use of animals in this area of research.